The effect of neighbourhood cohesion on mental health across sexual orientations: A longitudinal study. (November 2020) - Teo, Celine; Chum, Antony
Abstract: Given the persistent mental health disparities between sexual minorities and the general population, social epidemiological research should address this disparity by investigating the differential impact of neighbourhood social environments across sexual orientations. There is growing evidence that neighbourhood cohesion, conceptualized as a sense of belonging and social connection, is an important social determinant of mental health in the general population, but little is known about its impact across sexual orientations. Using data from the UK household longitudinal study (2009-2018) including waves 1, 3, 6, and 9 ( n = 52, 903), this paper examined the longitudinal relationship between neighbourhood cohesion and mental health (using GHQ-12) across sexual orientations. A fixed-effect regression approach was taken to model the within-person change over time in GHQ predicted by neighbourhood cohesion with disaggregated analyses by gender and sexual orientation. Across all sexual orientations and genders, individuals who experienced an increase in neighbourhood cohesion also saw an improvement in their mental health over time. Moreover, the effect of neighbourhood cohesion on mental health over time differed by sexual orientation. Each 1-point increase in neighbourhood cohesion (on a 5-point scale) lead to mental health improvements of -0.8 GHQ score (95%CI -0.89 to -0.71) for heterosexual males at the lowest end, and up to -1.71 GHQ score (95%CI -2.31 to - 1.11) for homosexual men at the highest end. Given that the study demonstrates notable differences in the effects of neighbourhood social environment across gender and sexual orientations, this points to the need to consider sexual orientation (along with gender) as a key modifier in research involving neighbourhood effects. Future studies should evaluate the effectiveness of specific policies aimed at improving neighbourhood social environment for sexual minorities to help close mental health disparities. Highlights: Neighbourhood cohesion is an important social determinant of mental health. The impact of neighbourhood cohesion across sexual orientations is unknown. The effect of neighbourhood cohesion on mental health over time differed by sexual orientation. Mental health of gay men was most affected by neighbourhood cohesion. Need to consider sexual orientation as a key modifier in future neighbourhood effects research.